White Matter Hyperintensities and Functional Outcomes in Patients With Cerebral Hemorrhage: A Systematic Review and Meta-Analysis - You, Qian; Yang, Yi; Hu, Hongtao (Frontiers in Neurology, 2022)
Background and Objectives There are controversies about white matter hyperintensities (WMH) and the prognosis of spontaneous intracerebral hemorrhage. Our objective is to investigate the relationship between WMH with functional outcome after intracerebral hemorrhage(ICH). Methods We systematically searched PubMed, EMBASE, and Cochrane Library databases from inception through 2021.8.10 without any restriction of countries. Articles investigating the relationship of WMH and functional outcome as well as mortality of patients with spontaneous ICH were included. We extracted relevant data and evaluated study quality with the Newcastle-Ottawa Scale. We pooled odds ratio (OR) for the presence and different severities of WMH with random effects models using STATA. Results A total of 10584 patients with ICH in 18 studies were included in the analysis. Moderate/severe WMH were related to poor functional outcome (OR 1.805, 95%confidence interval(CI) 1.320-2.469) and all-cause mortality (OR 3.27, 95%CI 2.07-5.18) after ICH. Besides, increasing severity of WMH were also related to poor functional outcome (OR 1.34, 95%CI 1.17-1.53) and all-cause mortality (OR 1.62, 95%CI 1.39-1.90). The pooled data did not find the relationship between the presence of WMH and poor functional outcome (OR 2.54, 95% CI 0.91-7.05) after ICH. The results remained stable after adjusting for age, hematoma volume, stroke as well as intraventricular hemorrhage. Conclusions We found moderate and severe WMH were related to poor functional outcome and all-cause mortality after ICH. High quality prospective studies are still needed.